(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic suppurative otitis media (CSOM) is an inflammatory process in the middle ear cleft. When there is attic or marginal perforation it is called the atticoantral variety of COSM which is manifested as foul smelling aural discharge and hearing impairment. In Bangladesh, chronic suppurative otitis media (CSOM) is a common disease in clinical practice. Objective: The aim of this study was to find out the clinical presentation of atticoantral chronic suppurative otitis media (CSOM) in defence personnel and their families. Methods: A retrospective study was carried out in the Department of ENT and Head-Neck Surgery, Combined Military Hospital (CMH), Dhaka from 01 April 2017 to 31 December 2019.Forty seven patients of Atticoantral variety of CSOM were included by matching inclusion and exclusion criteria. Results: Majority of the patients presented in the second and third decade of life(11-20 years: 29.79%, 21-30 years: 44.68%). All the patients belonged to the soldiers and their families. The maximum numbers of patients were from rural area(51.06%), completed only primary education (48.94%). Most of them lived in a kutcha building. Almost all the patients presented with multiple symptoms. Discharge from ear(s) (100%), and hearing impairment (82.97%) were the leading features. Only (2.14%) had extracranial complication and there was no intracranial complication. Most of the patients were having unilateral atticoantral CSOM, in the right side (61.70%), left side (36.17%) and only one (2.12%) had bilateral involvement. Audiometric tests were done in 100% of the patients and found; mild deafness (19.14%), moderate deafness (78.72%) and moderately severe deafness (2.14%). Conclusion: The frequency of chronic suppurative otitis media is higher in the younger age group and lacking of education. By increasing health awareness of the general people and early diagnosis of atticoantral CSOM and timely surgical intervention may be helpful to eradicate the disease and prevent complications. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 136-141